Jogos digitais e cognição social de crianças: um estudo experimental - Scienza, Livia (2020)
In the last decade, the number of new digital games of various genres has grown a lot, eminently after the creation of game management platforms and after the dissemination of eSports. Digital games, beyond their entertainment purpose, are already used in schools, hospitals, and psychotherapeutic environments as rehabilitation tools and to promote cognitive and behavioral skills. Studies evaluating the impact of this form of media on users have conducted since the popularization of the first games in the 70s. However, the evidence that games can mediate interpersonal relationships, as well as promote or inhibit prosocial and empathic behaviors is still recent. The focus of previous studies was the possible associations with increased aggressive behavior and desensitization to violence. And although most consumers of digital games are young people and adults, the “digital natives” born in this century have immediate access to interactive media. For this reason, many researchers have recently investigated the way in which children and adolescents are affected by these media. In particular, more studies investigating the impact of games on sociocognitive and social skills should be conducted. Following this direction, the present work aimed to investigate a possible relationship between exposure to three categories of digital games (Neutral, Prosocial and Competitive) and prosocial behavior. A second goal was to test possible moderating effects of empathy and theory of mind skills on this relation. Fifty-seven children (9 to 12 years old) participated and were randomly distributed into three groups: G1 = neutral game; G2 = competitive game, G3 = prosocial game. Each group played a different type of video game. Prior to playing the games, all participants were assessed by a social cognition task (Faux Pas Task) and an empathy scale (Bryant's Empathy Scale for Children and Adolescents). Following that and on another day, each participant was invited to play, for 20 minutes, the digital game representative of their category group. Finally, right after playing the game, children were invited to participate in an adapted version of the Dictator's Game that involves the sharing of resources. Games of all categories had a pre-selection stage and were evaluated by 18 judges that were either Psychology undergraduate/ graduate students or university students from a game development outreach group. One game for each category was selected. Analyses did not reveal a significant gender or age effect on empathy scores, theory of mind scores and number of donated stickers. However, a significant age effect (i.e., school year) was found for the number of stickers shared, with older children sharing more stickers than younger ones. Nonetheless, there was a trend toward a significant moderating effect of empathy and theory of mind scores on the relationship between game category and number of stickers shared by the participants. More specifically, playing a prossocial, neutral or competitive videogame for 20 minutes does not necessarily impact the predisposition of children to engage on prossocial behavior. It is possible, nevertheless, that more empathic children with a more developed theory of mind may have an increased predisposition to share stickers compared to other children. Future studies should explore further whether these variables (empathy and theory of mind) or other variables can, in fact, explain part of the variation in prosocial behavior after exposure to different types of digital games. However, the present work contributes to the advancement of this line of research in Brazil as it is the first study to investigate possible effects of three different types of digital game on prosocial behavior in school-age children. The results suggest a promising direction of investigation that should be better explored by researchers in Brazil.